Bioactive natural products with anti-herpes simplex virus properties - Hassan, Sherif T S; Masarčíková, Radka; Berchová, Kateřina (The Journal of pharmacy and pharmacology, 2015)
OBJECTIVES: In this review, we highlight and summarise the most promising extracts, fractions and pure compounds as potential anti-herpes simplex virus (HSV) agents derived from microorganisms, marine organisms, fungi, animals and plants. The role of natural products in the development of anti-HSV drugs will be discussed. KEY FINDINGS: Herpes simplex viruses (HSV-1 and -2) are common human pathogens that remain a serious threat to human health. In recent years, a great interest has been devoted to the search for integrated management of HSV infections. Acyclovir and related nucleoside analogues have been licensed for the therapy that target viral DNA polymerase. Although these drugs are currently effective against HSV infections, the intensive use of these drugs has led to the problem of drug-resistant strains. Therefore, the search for new sources to develop new antiherpetic agents has gained major priority to overcome the problem. SUMMARY: Natural products as potential, new anti-HSV drugs provide several advantages such as reduced side effects, less resistance, low toxicity and various mechanisms of action. This paper aims to provide an overview of natural products that possess antiviral activity against HSV.
Keywords: antiviral agents; natural products; antivirové látky; racionální návrh léčiv; Herpesvirus 1, Human; Herpes Simplex; herpes simplex; Biological Products; Animals; Antiviral Agents; lidé; Drug Resistance, Viral; bioactive compounds; Humans; zvířata; nucleoside analogues; herpes simplex virus; lidský herpesvirus 1; Drug Design; virová léková rezistence; biologické přípravky